Peningkatan kemampuan membaca permulaan siswa kelas 1 SDN 01 Sengare melalui penggunaan media kartu kata - Ika Khaeriyah (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The research was designed in the form of classroom action research which was carried out in two cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. Research data were collected through observation and tests at the end of each cycle. Based on the results of the research and discussion of classroom action research, it is shown that through the medium of word cards students' initial reading ability can be increased. This can be seen through the first cycle of completeness, it is known that 11 students who are declared complete with a percentage of 68.75% and students who do not complete as many as 5 people with a percentage of 31.25%; with an average score of 69.5. The percentage of completeness and the average value in the first cycle have not reached the indicators of research success so that it needs to be continued in the second cycle. The results of the second cycle showed students who completed 14 students with a classical completeness percentage of 87.5% with an average value of 90.5. In addition, student activity during the learning process also increased from 70% in the first cycle to 85% in the second cycle. From the results obtained, the researcher concluded that word card media could improve the early reading ability of 1st graders at SDN 01 Sengare.